Analiza plavalnega znanja pri sprejemnem postopku za vpis na študij Fakultete za šport - Virag, Jure (Šport (Ljubljana), 2016)
The aim of the study was to assess the swimming knowledge of candidates in the acceptance procedure at the University of Ljubljana, Faculty of Sport. Based on the candidates' gender we tried to establish, how fast the candidates swim and which swimming style they use. We also had the desire to figure out, how these two variables change within groups: that were accepted to their desired study programme from those who were not accepted; from different study programmes. With the help from the results of our analysis we set the criteria for evaluating times, which were achieved in the swimming test for the 100 metres freestyle.
Keywords: acceptance procedure; plavalni način; plavalno znanje; plavanje; results; rezultati; sport; sprejemni postopek; swimming; swimming knowledge; swimming style; šport; testi; testing